1963
DOI: 10.1038/bjc.1963.88
|View full text |Cite
|
Sign up to set email alerts
|

The Carcinogenic Action of Aflatoxin after its Subcutaneous Injection in the Rat

Abstract: Images Figs. 1-3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
5

Year Published

1966
1966
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(28 citation statements)
references
References 7 publications
1
22
0
5
Order By: Relevance
“…The administration of patulin subcutaneously twice a week for 15 months showed the development of malignant tumor cells in the area of administration which proved the carcinogenic effect of this mycotoxin. It can by hypothesized in humans as well (64,(194)(195)(196) although the carcinogenic effect of patulin was not confirmed by Osswald at al (197), patulin was confirmed to be toxic to the mice born to patulin treated mothers and deaths occurred in both males and females.…”
Section: Mycotoxins and Their Carcinogenicitymentioning
confidence: 99%
“…The administration of patulin subcutaneously twice a week for 15 months showed the development of malignant tumor cells in the area of administration which proved the carcinogenic effect of this mycotoxin. It can by hypothesized in humans as well (64,(194)(195)(196) although the carcinogenic effect of patulin was not confirmed by Osswald at al (197), patulin was confirmed to be toxic to the mice born to patulin treated mothers and deaths occurred in both males and females.…”
Section: Mycotoxins and Their Carcinogenicitymentioning
confidence: 99%
“…The four naturally occurring AFs, aflatoxins B1 (AFB1), B2 (AFB2), G1 (AFG1), and G2 (AFG2), when administered as mixtures, were a potent class of animal hepatocarcinogens (2-6). They have been also associated with neoplastic formations in tissues and organs other than the liver (3,(6)(7)(8)(9).Tests with rats (10) and rainbow trout (11) have revealed that AFB1 is a potent hepatocarcinogen; AFG1 is also considerably carcinogenic, but AFB2 and AFG2 possess much lower activity. Recent studies on the metabolism of AFB1 have resulted in the isolation and identification of numerous metabolites, all of minor structural variations but significantly different biological activity relative to the parent compound (12).…”
mentioning
confidence: 99%
“…exposure to AFB,, so, with this mode of administration, it is possible that unmetabolized AFB, could reach bone marrow cells. AFB, is also carcinogenic in extrahepatic tissues: it induces carcinomas at low incidence in the glandular stomach (10) and fibrosarcomas are inducible at the site of injection when AFB, is given several times in doses of 50 and 500 /tg subcutaneously (12). However, the absence of mutagenic activity after oral application most likely is due to the efficient activation of AFB, in the liver, where the chemical is converted to the ultimate carcinogen, the reactive 2,3-oxide (20), in a single, cytochrome P-450-dependent step and interacts mainly at sites where these enzymes are accumulated.…”
Section: Discussionmentioning
confidence: 99%